Perceived stress and high fat intake: A study in a sample of undergraduate students - Vidal, E. Jair (2018)
Objectives Different studies have reported the association between perceived stress and unhealthy diet choices. We aimed to determine whether there is a relationship between perceived stress and fat intake among undergraduate medical students. Methods/Principal findings A cross-sectional study was performed including first-year medical students. The outcome of interest was the self-report of fat intake assessed using the Block Screening Questionnaire for Fat Intake (high vs. low intake), whereas the exposure was perceived stress (low/ normal vs. high levels). The prevalence of high fat intake was estimated and the association of interest was determined using prevalence ratios (PR) and 95% confidence intervals (95% CI). Models were created utilizing Poisson regression with robust standard errors. Data from 523 students were analyzed, 52.0% female, mean age 19.0 (SD 1.7) years. The prevalence of high fat intake was 42.4% (CI: 38.2%–46.7%). In multivariate model and compared with those with lowest levels of stress, those in the middle (PR = 1.59; 95%CI: 1.20–2.12) and highest (PR = 1.92; 95%CI: 1.46–2.53) categories of perceived stress had greater prevalence of fat intake. Gender was an effect modifier of this association (p = 0.008). Conclusions Greater levels of perceived stress were associated with higher fat intake, and this association was stronger among males. More than 40% of students reported having high fat consumption. Our results suggest the need to implement strategies that promote decreased fat intake.